Eco-Traditions and Local Wisdom of Nyapu Kabuyutan in Situs Gunung Payung, Sirnajaya Village - Maulana, Fahmi; Brata, Yat Rospia; Sudarto, Sudarto (Universitas Galuh, 2025)
This study examines Eco-Traditions and local wisdom within the framework of eco-management through an ethnographic study of Traditional Ecological Knowledge (TEK) in the Nyapu Kabuyutan tradition at the Gunung Payung Site, Sirnajaya Village. A qualitative approach using ethnographic methods was used to understand the meaning of rituals and environmental management practices that have been passed down from generation to generation. Data was collected through participatory observation, in-depth interviews, and documentation. The results of the study show that the Nyapu Kabuyutan tradition not only functions as a cultural ritual but also as an ecological management mechanism that supports local environmental conservation through inherent wisdom values. This study proposes the integration of local wisdom into sustainable environmental management policies.